Study on lubrication effect on motorbike chain transmissions. Issue 5 (8th August 2016) - Palazzetti, Roberto; Yan, Xiu Tan
Abstract : Purpose: This paper examines motorbike's chain transmission, focusing on chain lubrication and its effect on the temperature, efficiency and vibrations of the transmission. Purpose of the paper is to compare transmission's performances under three different lubrication conditions: (i) chain not lubricated at all, (ii) chain lubricated with a spray PTFE addicted lube, and (ii) chain lubricated with a mineral oil at every minute of the test. Design/methodology/approach: An experimental campaign has been performed running a chain under the three above lube conditions at different speeds with the purposes of: (A) measuring the effect that each lube conditions has on temperature, on vibrations and on the efficiency of the transmission, and (B) identify the best conditions for practical use. A test rig has been designed and manufactured for the purpose, and temperature, transmission's efficiency and vibrations have been recorded during the tests by using a thermocamera, a dynamometer and an accelerometer respectively. Findings: Results showed that a proper lubrication is desirable. Additionally using a continuous lubrication with a mineral oil lubricant leads to better transmission compared to the use of the spray PTFE from the efficiency and thermal points of view. Originality/value: This work presents an experimental investigation on the effect of two different kind of lubrication form motorbike chain on transmission's efficiency. The findings are still valid for different applications of chain transmission in dirty environments. Novelty of the paper is following highlighted: 1) this is the first work scientifically facing the important topic of lubrication of chain in dirty environments, particularly of motorbike chain; 2) a complete analysis of thermal and mechanical effect due to presence of lubricant has never been shown; 3) different kind of lubricant have been used and their effect has been separately highlighted.